A bibliometric review on knowledge management in tourism and hospitality: Past, present and future trends - Fauzi, M. A. (Emerald Publishing, 2022)
Purpose: The purpose of this study is to review the plethora of studies on knowledge management (KM) in the hospitality and tourism. The purposes of this paper through a bibliometric analysis via the VOSviewer tool are to analyze the current research stream and to assess emerging trends in KM in the tourism and hospitality field. Design/methodology/approach: A total of 1,732 publications with 65,150 cited references were retrieved from the Web of Science to uncover the structure and intellectual base of studies in tourism with a KM perspective. Three bibliometric analyses were performed using VOSviewer software (citation, co-citation and co-occurrence of keywords); this study aims to uncover the knowledge structure of the past, current and future trends based on the bibliographic database by assessing the most influential past publication; determining the structure of the co-cited publications; and evaluating emerging trends for future studies. Findings: This study produced two ground-breaking research streams inductively evaluated from the three bibliometric analyses: KM and digital technology; and innovation in tourism. Furthermore, the pressing issue of sustainability in tourism from the perspective of KM would be a crucial aspect in the tourism field. These streams would provide fundamental knowledge-based and further enhance the assimilation of KM within the tourism sector. The outcome would facilitate future scholars to link important tourism topics to benefit the tourism industry facing a competitive and challenging business environment. Research limitations/implications: This study contributes to the current theoretical understanding through thematic knowledge mapping of KM and the tourism and hospitality field. Originality/value; To the best of the author’s knowledge, this study is the first to apply bibliometric analysis to the tourism and KM field by providing a basis for the most significant issue in tourism and the essence of emerging topics and trends.